Modelo conceitual para sistematização e avaliação de indicadores de sustentabilidade para sistemas agroflorestais no contexto da gestão de recursos hídricos - Machado Júnior, José de Aquino (2019)
In recent years, forest recovery has been one of the main activities in watershed management, since its use can promote environmental improvements in the hydrological cycle as well as socioeconomic enhancements thus helping in sustainable territorial development. In this context, the use of Agroforestry Systems - SAFs is one of the main forest recovery strategies, because they are considered more sustainable than others forest cover and in addition, they are an alternative to the intensive production systems. In spite of the importance of the SAFs in the forest recovery theme, in general, the studies that consider the sustainability assessment do not contemplate many aspects/factors that could influence their application by potential rural producers. Due to the benefits of these systems this work aimed at enlarging knowledge about factors associated with their sustainability, as well as to establish guidelines for the improvement of its application. Therefore, a literature review was carried out as well as an observation of the State Program for Increasing Forest Coverage - Reforestation and the State Policy for Water Resources of Espírito Santo. Then these data were related to the SAFs by the use of a technic based on the methodological framework titled "Sustainability of Agriculture and Natural Resources - SARN ", a conceptual model was developed for the systematization and evaluation of sustainability indicators for SAFs. As a result, 98 indicators were obtained and systematized in levels of descriptors, significant elements, significant categories and evaluation dimensions, the distribution by dimension were: Environmental - 40 indicators (41%); Sociocultural - 28 indicators (29%); Economic -18 indicators (18%) and Political Institutional - 12 indicators (12%). The proposed structure for the systematization of the indicators provides a qualitative and systemic evaluation of the sustainability of the resources and the operations involved in the SAFs that subsidises guidelines for improving the use of SAFs in different situations in the watersheds. Most of the indicators are quick implementation and not onerous as well as they depend on direct visual evaluations and interviews. For the minority of the indicators more calculus and a complex laboratory analyzes will be needed